STUDI KASUS PENERAPAN EVIDANCE BASE NURSING TERAPI MUSIK NATURE SOUNDS TERHADAP KUALITAS TIDUR PERAWAT DI RUANG CEMARA 1 RUMAH SAKIT BHAYANGKARA TK. I R. SAID SUKANTO - Tsilmi Adhari, (2022)
Rest and sleep play an important role because it is a basic need from a physiological point of view, sleep quality can have a major influence on nurse performance. Good quality sleep will improve health, restore freshness and function in the body's organs. Based on the assessment of 8 nurses, it was found that 5 nurses (62.5%) were in the bad category, 3 other nurses (37.5%) were in the good category, so the author aims to manage sleep quality by applying nature sounds music therapy to nurses. The first step in the case study was to distribute the pre-test using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. After obtaining data on the sleep quality of nurses, the next step was to implement and implement nursing interventions using music therapy nature sounds. This therapy uses natural music such as the sound of waterfalls, wind, birds chirping and rain which is given for 30 minutes using a speaker with a volume of 60-70 dB which is placed ± 1 meter from the intervention object for three consecutive days. The final stage is an evaluation, which is carried out with a posttest and the results show that nature sounds music therapy can improve sleep quality for nurses. The author hopes that nature sounds music therapy can continue to be implemented for nurses to improve sleep quality so that nurses' performance can increase